Етногенез слов’ян у світлі археологічних джерел України III—I тис. до н. е. - Максимов, Є.В. (Археологія, 1994)
У статті висвітлюються генетичні зв'язки між численними археологічними культурами північної частини Україна доби бронзи та раннього заліза, які в III—I тис. до н. е. являли історичні ланки складного і тривалого процесу становлення та розвитку слов'янського етносу на найранішому етапі його існування. Славяне под своим именем впервые стали известны византийским историкам 6 в. — Иордану и Прокопию Кесезринскому. Глубины же славянской истории не освещены письменными источниками, они вызывают много вопросов и являются предметом острых дискуссий.
В решении этой проблемы существенную роль играют археологические материалы, количество которых непрерывно возрастает. Анализ этих материалов, осуществленный по методу ретроспективного типологического сравнения важнейших элементов культуры, показывает, что глубины славянской истории синхронны позднему периоду трипольской культуры, однако связаны не с нею, а украинскими регионами культуры шнуровой керамики, в первую очередь — среднеднепровской культурой конца ІІІ — начала ІІ тыс. до н. э.
Начиная с этого времени и вплоть до конца I тыс. до н. э. тянется цепочка генетически родственных культур эпохи бронзы и раннего железного века лесостепной и полесской части преимущественно правобережной Украины, составляющих звенья славянского этногенеза. Это — восточноготшинецкая и сосницкая культуры эпохи средней бронзы, затем - лебедовская и белогрудовская культуры поздней поры бронзового века, милоградская и правобережная (типа Хотова) культура скифского периода.
Все эти культуры имели контакты — иногда достаточно тесные с соседними индоевропейскими племенами балтов, германцев, фракийцев и иранцев, что нашло свое отражение в материалах таких культур этого периода как Комаровская культура средней бронзы или более поздние высоцкая, чернолесская или подгорцевская культуры, наличие которых указывает на европейский характер процесса формирования древнеславянского этноса. Slavs have become known under their own name first to Jordan and Prokoptus Caessarian, Byzantine historians of the 6Ш cent. History of Slavs lacks a thorough insight into its depth and is not treated well by written sources. So, it offers a fertile field for ressearcn and is a subject of acute discussions.
Solution of this problem is significantly promoted by archaeological findings which amount is continuously' growing. The analysis of these findings made by the method of retrospective typological conparison of the most inportant cultural elements has shown that the roots of Slavonic history go back, to she late period of the Tripolian culture but are not related to It. They are related to Ukrainian regions of cord-decorated pottery, mainly, to the Mid-Dnieper culture of the late 3d and early 2nd millennium B.C.
From that very period and up to the end of the 1st millennium Б. C, a chain of genetically allied cultures of She bronze time and early iron period of the forest-steppe and Polessian part of primarily right-bank Ukraine is traced. These cultures are links of the Slavonic ethnogenesis. They are: east-Tshinetskaya and Sosnitskaya cultures of the mid bronze time; then follows Lebedevskaya and Belogrudovskaya cultures of the late bronze time, Miiogradskaya end right-bank (of the Khotov type) cultures of the Scythian period.
AJ1 those cultures had contacts, and sometimes rather close ones, with neighbouring Indo-European tribes of Baits, Germans, Frakians and Iranians, which is confirmed by findmgs of the cultures of that period, such as Komarovskaya culture of the mid brortxe or later Vysotskaya, Cher notes skaya or Podgortsevskaya cultures. Their presence shows a European type of the process of ancient Slavonic ethnos formation.